Epidemiology of NDM-Producing Enterobacteriaceae in Michigan. (October 2020) - Gill, Gurmat; Sandhu, Avnish; Polistico, Jordan; Awali, Reda; McNamara, Sara; Chopra, Teena
Abstract : Background: Carbapenem-resistant Enterobacteriaceae (CRE) are classified as an urgent antibiotic-resistant threat by the CDC, and they are listed on the critical priority list by the World Health Organization due to the lack of antibiotic treatment options. New-Delhi metallo-β-lactamase (NDM) is an emerging mechanism of carbapenem resistance in the United States. We sought to understand the risk factors and clinical characteristics of patients with NDM CRE in Michigan to improve surveillance. Methods: A retrospective descriptive study was conducted in collaboration with the Michigan Department of Health and Human Services (MDHHS). CRE isolates submitted to MDHHS between April 2014 and July 2019 were tested for the presence of NDM using CDC PCR protocols. Additional information on case demographics, laboratory results, healthcare and antibiotic exposure history, and travel history were collected. Results : In total, 30 NDM cases were identified in Michigan during the study period. Of these 30 cases, 15 (50%) were men, and the median age was 73.5 years (range, 20–88 20). Also, 2 of these patients (6.6%) were immunocompromised; 2 patients (6.6%) had had extensive abdominal surgery, and 2 patients (6.6%) had recurrent hospitalization. Furthermore, 12 case isolates (40%) were collected in outpatient settings, whereas 16 (53%) were collected from inpatient settings. In addition, 13 (43%) patients were admitted from home and 4 (13%) presented from an extended-care facility. Urine was the most common site of isolation in 19 of 30 (63%) cases, followed by blood and tissue culture in 4 of 30 (13%) each. Escherichia coli was the most common organism (17 of 30, 57%), followed by Klebsiella pneumoniae (9 of 30, 30%). Also, 15 of 30 cases (50%) had a recent history of international travel, and of these, 9 of 15 (60%) reported travel to India. Among these 15 cases, 12 (80%) sought medical care in the countries they visited. Two cases (6.6%) had a documented history of multidrug-resistant organism colonization or infection. The mortality rate was 6.6% (2 of 30). The mean time from admission to implementation of contact precautions was 7.3 days (range, 0–20). Conclusions: Suspicion of NDM CRE strains should remain high in patients with a travel history from areas known as major reservoirs of NDM. Delay in implementing contact precautions, as noted in the present study, can lead to a greater risk of transmission. Early detection and subsequent isolation of NDM patients are essential strategies for preventing transmission within healthcare facilities. Future efforts include performing whole-genome sequencing of these isolates to assist in identifying potential epidemiological links among the affected patients. Funding: None Disclosures: None